CLIMATE CRISIS AND THE WELL-BEING OF VULNERABLE GROUPS: A SOCIAL WORK PERSPECTIVE ON THE ELDERLY AND PERSONS WITH DISABILITIES (Proceeding of SINERGY, 2026)
The climate crisis has become an existential threat that disproportionately impacts vulnerable groups, particularly the elderly and people with disabilities. This study examines how climate change affects the well-being of these two groups through a systematic literature review approach with a social work perspective. The purpose of this study is to identify the impact of the climate crisis on the elderly and people with disabilities, analyze the specific vulnerabilities they face, and develop social work intervention strategies responsive to climate change issues. The research method used a systematic literature review by analyzing 45 articles from the Scopus, Web of Science, PubMed, and Google Scholar databases for the period 2015-2024. Inclusion criteria included peer-reviewed publications discussing the climate crisis, vulnerable groups, and social interventions with clear methodologies. The results show that the elderly face a high risk of extreme heat waves, natural disasters, and social isolation due to climate change, with mortality rates 2-3 times higher than those of the productive age group. Disability disclosures experience systematic barriers in accessing evacuations, inaccessible emergency information, and exclusion from disaster mitigation planning. Intersectional vulnerability arises when these two identities intersect with factors such as gender, race, social class, and geographic location. Social work practice needs to integrate a climate justice perspective by developing inclusive early warning systems, disability-friendly shelters, resilience-based community empowerment programs, and transformative policy advocacy. The study's conclusions emphasize the need for an ecological and transformative social work paradigm, integrating pro-climate policy advocacy with micro-practices that consider the vulnerability of intersectional marginalized groups in the face of the intensifying climate crisis.